Explanation about archetypes of bear in Mythology - Mendmaa, Pagmadulan (Studia Folclorica, 2024)
The article discusses Mongolian magical practices [dom] and animal-based medical remedies, highlighting the use of bear-related remedies. We aim to gather motifs and characters from Mongolian mythology associated with these magics [dom] and intend to interpret them. Mircea Eliade, a scholar of religion and mythology, has explained through the rituals of “making mandalas” in Indian and Tibetan traditions that myths concerning the beginning of the World, illnesses, and remedies are retold during rituals and doms to facilitate healing. Specifically, the belief was that by reconstructing the Cosmos, a wholly rejuvenated individual is born into that world, and simultaneously, the ailment afflicting the patient becomes healthy. Similarly, one can notice that Mongols medicinal practices and animal-based remedies, especially bears, are intricately intertwined with Mongolian myths regarding the genesis of animals. One aspect involves a character and motif from a Mongolian myth depicting an individual of great courage and strength transformed into to bear. On the flip side, there are magic/remedies associated with utilizing bear organs such as the liver, bile, and blood for medicinal purposes, as well as doms incorporating bear body parts like claws, julch, el etc. for healing practices. The act of using any part of the bear’s organs for healing purposes can be seen as a recreation of the myth that “A bear was a person.” This concept suggests that when a person transforms into a bear, there is a notion of their body and organs being transferred to a healthy “person.” This notion serves as the archetype underlying these myths. Домог зүй дэх баавгайн уг дүрийг тайлан тайлбарлах нь Хураангуй: Тус өгүүлэлд монголчуудын анагаан илаарьшуулах зорилготой домуудыг баавгайтай холбогдох домоор төлөөлүүлэн авч үзээд, эдгээр домын утга учрыг монгол домог зүйн дүр, өгүүлэмжээс хайн олж, тайлан тайлбарлахыг зорьжээ. “Домог өөрөө анагаан илаарьшуулах үүрэгтэй” хэмээсэн шашин, домог зүй судлаач Мирча Элиадегийн үзлээр аливаа анагаан эдгээх зорилго бүхий зан үйл, дом нь эртний хүмүүсийн бүтээн туурвилын охь дээж болсон домгийг дахин бүтээж байдаг гэдгийг Энэтхэг, Төвөдийн “мандала бүтээх” зан үйлээр жишээлэн тайлбарласан байдаг билээ. Тодруулбал, орчлон ертөнц (космос)-ийг дахин бүтээхтэй адил хэмжээнд сэтгэж, мандала-г бүтээснээр ертөнц дээр анхлан үүсэн бүрэлдсэн цоо шинэ, эрүүл саруул хүнийг ч хамтад нь бүтээж буй хэрэг бөгөөд ингэснээр өвчтөний өвчин эмгэг ч арилдаг гэж үздэг аж. Үүнтэй нэгэн адилаар монголчуудын амьтны эд эрхтнээр анагаах олон төрлийн арга ухаан болон домын зүйлс нь амьтны гарал үүслийн тухай монгол домогтой нарийн холбогдож буйг ажиглаж болно. Нэг талаар эр зориг, хүч тэнхээ бүхий нэгэн байгаад баавгай болсон хэмээх монгол домгийн дүр, өгүүлэмж байхад, нөгөө талд баавгайн эд эрхтнээр сэлбэн засах (элэг, цөс, цус г.м), баавгайн эд эрхтнээр домнох (сарвуу, жулч г.м) домууд байгааг холбон тайлбарлахдаа, баавгайн аливаа эд эрхтнийг ашиглан эрүүл саруул болж буй нь “баавгай хүн байсан” хэмээх домгийг “дахин бүтээж” буй явдал бөгөөд баавгай болох үеийн эрүүл чийрэг “тэр нэгэн хүн”-ий бие эрхтэнд шилжиж буй мэт үзэл төсөөлөл нь эдгээр домын “уг дүр (архетип)” байж болно гэсэн санааг зохиогч дэвшүүлжээ. Түлхүүр үг: Баавгай, домог, уг дүр, өгүүлэмж, өвчин, эм, дом, Мирча Элиаде